Analisis Bibliometrik Perkembangan Penelitian Tentang Pondok Pesantren Menggunakan Vosviewer - Darmawan, Budi; Afrinaldi, Rori; Iqra Pandu Wijaya (UNILIB : Jurnal Perpustakaan, 2024)
This paper aims to find out the development of research on the development of Islamic boarding schools by searching for data on Dimensions using the Vosviewer application. This paper uses a descriptive bibliometric analysis method by analyzing Dimensions data on the Vosviewer application about the development of Islamic boarding schools. The results of the research in this paper are based on co-authorship (author) and co-occurrence (keywords). Bibliometric analysis was carried out using Vosviewer. There are 19,200 data that have been collected through published metadata. Based on the results of bibliometric mapping research using Vosviewer using network visualization, overlay and density, it can be concluded that in the time span from 2014 to 2023, the search for the development of Islamic boarding schools continues to experience developments in fluctuating research publications. Mapping was also carried out through keywords or co-occurrence, and succeeded in identifying a relationship between scientific concepts and the 4 dominant clusters, such as Islam, education, values, student, Islamic boarding school, religion, woman, thought, and others.